Performance of gender-based violence case management at the asociación larense para la planificación familiar (ALAPLAF) (Revista Científica Compendium, 2025)
This social study adopts a gender perspective and a managerial approach within third-sector organizations. Specifically, it addresses the “Asociación Larense para la Planificación Familiar” with the aim of analyzing the performance of the Case Management Service for Gender-Based Violence (GBV). The methodology follows a quantitative approach with a descriptive, non-experimental, field, and cross-sectional design. The population and sample were equivalent, determined by purposive and census criteria, consisting of eight (8) female employees of the institution. For data collection a survey was used in the form of a questionnaire with closed questions and a Likert scale. The internationally recognized Gender-Based Violence Information Management System (2017 Edition) was adopted as a reference. The instrument was validated through expert judgment to ensure coherence, relevance, and clarity. Data processing and interpretation were supported by descriptive statistics. The findings demonstrate that the organization implements a high-level approach to GBV case management, contributing to the mitigation of this social issue in the State of Lara.
Keywords: administrative processes; case management; gender-based violence; staff qualification